Find the sum of (–4 + i) and (10 – 5i).a. –3 + 5i

b. –3 - 5i

c. 6 – 4i

d. 6 – 6i

Answers

Answer 1
Answer: To add complex numbers, it is necessary to group the similar terms (real and real, then imaginary and imaginary) before simplifying. This will be done as follows:

(-4 + i) + (10 - 5i)

Grouping similar terms:
(-4 + 10) + (i - 5i)
6 - 4i

From the choices, the correct answer is C.
Answer 2
Answer:

C on edgenutiy just took it


Related Questions

What multiplies to 16 and adds to negative 12
Solve the following equation |-5x+20|=-15 for x
Faye owned 1,300 shares of Wonderband Corp. Last week, a 2-for-1 split was executed. The pre-split price per share was w dollars. a. Determine the number of shares Faye owned after the split. b. Write an algebraic expression for the price per share after the split. c. Express the total value of the Wonderband stock Faye owned algebraically after the split.
I want a good person who no really good at math and solve it
Find all real zeros of the function. f(x)=4(x^2-1)(x-3)(x+3)^2

NEED QUICK 50 POINTS

Answers

Answer:

y = 80

x = 5

Hope this helped :)

Step-by-step explanation:

Lets say x + 5 so,

y = 8(5) + 12

y = 40 + 12

y = 52 so now we go back to the top equation which would be,

16(5) - 2(52) = -24

80 - 2(52) = -24

80 - 104 = -24, true

Therefore, any number you put in will still get you -24 so your answer is correct if you do substitution right.

Answer:

y = 80

x = 5

Hope this helped :)

Step-by-step explanation:

Lets say x + 5 so,

y = 8(5) + 12

y = 40 + 12

y = 52 so now we go back to the top equation which would be,

16(5) - 2(52) = -24

80 - 2(52) = -24

80 - 104 = -24, true

Therefore, any number you put in will still get you -24 so your answer is correct if you do substitution right.

Simplify (2n + 5) - (3n + 7) + (4n - 9).
-3n - 11
3n - 11
-3n + 11
3n + 11

Answers

☸ We are going to simplify this Step-By-Step. ☸

☸ First here is the question you ask:

2n
+5
(3n+7)
+4n
−9

☸ Lets start with this:

=2n+5+3n+−7+4n+−9

☸ Now lets Combine Like Terms:
(Pst the bold stuff is for Combining Like Terms)

=2n+5+3n+−7+4n+−9

=(2n+3n+4n)+(5+−7+−9)

☸ Your answer shall be:

=3n+−11

☸Hope this helps!

How would you find the real solution, by using the quadratic formula.
x^2-4x+2=0

Answers

x^2-4x+2=0 \n \na=1 \n b=-4 \n c=2 \n b^2-4ac=(-4)^2-4 * 1 * 2=16-8=8 \n \nx=(-b \pm √(b^2-4ac))/(2a)=(-(-4) \pm √(8))/(2 * 1)=(4 \pm √(4 * 2))/(2)=(4 \pm 2√(2))/(2)=(2(2 \pm √(2)))/(2)=2 \pm √(2) \n\boxed{x=2-√(2) \hbox{ or } x=2+√(2)}
x^2-4x+2=0\nx^2-4x+4-2=0\n(x-2)^2=2\nx-2=\sqrt2 \vee x-2=-\sqrt2\nx=2+\sqrt2 \vee x=2-\sqrt2

7/8 is equvlent to what over 24

Answers

We know that 8 x 3= 24 
7/8=?/24 
7 x 3=21 
So the answer is 3 
3/24 

Use technology or a z-score table to answer the question.The number of baby carrots in a bag is normally distributed with a mean of 94 carrots and a standard deviation of 8.2 carrots.

Approximately what percent of the bags of baby carrots have between 90 and 100 carrots?

Answers

Answer: 46%

Step-by-step explanation:

Since the number of baby carrots in a bag is normally distributed, we would apply the formula for normal distribution which is expressed as

z = (x - µ)/σ

Where

x = the number of baby carrots in the bag.

µ = mean

σ = standard deviation

From the information given,

µ = 94 carrots

σ = 8.2 carrots

The probability that a bag of baby carrots have between 90 and 100 carrots is expressed as

P(90 ≤ x ≤ 100)

For x = 90,

z = (90 - 94)/8.2 = - 0.49

Looking at the normal distribution table, the probability corresponding to the z score is 0.31

For x = 100,

z = (100 - 94)/8.2 = 0.73

Looking at the normal distribution table, the probability corresponding to the z score is 0.77

Therefore,

P(90 ≤ x ≤ 100) = 0.77 - 0.31 = 0.46

The percent of the bags of baby carrots that have between 90 and 100 carrots is

0.46 × 100 = 46%

Solve the following system of equations?x + 3y - z = 2
x - 2y + 3z = 7
x + 2y - 5z = -21
a)(2, 3, 5)
b)(-2, 3, 5)
c)(2, -3, 5)
d)(2, -3, 5)

Answers

1x + 3y - 1z = 2    ⇒ 1x + 3y - 1z = 2
1x - 2y + 3z = 7    ⇒ 1x - 2y + 3z = 7
1x + 2y - 5z = -21             5y - 4z = -5
                                                                     5y - 4z = -5   ⇒ -20y + 16z = 20
1x + 3y - 1z = 2                                          -4y + 8z = -28 ⇒ -20y -  40z = -140        1x - 2y + 3z = 7     ⇒ 1x - 2y + 3z = 7                                              -24z = -120
1x + 2y - 5z = -21 ⇒ 1x + 2y - 5z = -21                                            -24      -24
                                       -4y + 8z = -28                                                  z = 5
                                                                                                    5y - 4(5) = -5
                                                                                                      5y - 20 = -5
                                                                                                           +20   +20
                                                                                                             5y = 15
                                                                                                              5      5
                                                                                                               y = 3
                                                                                                x + 3(3) - 5 = 2
                                                                                                    x + 9 - 5 = 2
                                                                                                         x + 4 = 2
                                                                                                              -4  -4
                                                                                                               x = -2
                                                                                                      (x, y, z) = (-2, 3, 5)
The solution to the answer is B. (-2, 3, 5).